CEO Narcissism and Global Performance Variance in Multinational Enterprises: The Roles of Foreign Direct Investment Risk‐Taking and Business Group Affiliation. (4th February 2022) - Lee, Jeoung Yul; Ha, Yoo Jung; Wei, Yingqi; Sarala, Riikka M.
Abstract: This study examines key mechanisms through which CEO narcissism influences global performance variance in the context of Asian emerging market multinational enterprises. Building on the contextual reinforcement model of narcissism and the cushion hypothesis, we focus on the role of foreign direct investment (FDI) risk‐taking and business group affiliation (BGA). We test our moderated mediation model on data from 149 South Korean multinational enterprises from 2006 to 2016. The results show that CEO narcissism is positively associated with FDI risk‐taking. The effect of CEO narcissism on global performance variance is mediated by FDI risk‐taking. Furthermore, BGA moderates the above‐mentioned relationships. Our findings offer important contributions to the international business and CEO narcissism literatures.